The population of hot subdwarf stars studied with Gaia. II. The Gaia DR2 catalogue of hot subluminous stars - Geier, S.; Raddi, Roberto; Fusillo, N. P. Gentile; Marsh, T. R. (Astronomy & Astrophysics, 2019)
Based on data from the ESA Gaia Data Release 2 (DR2) and several ground-based, multi-band photometry surveys we have compiled an all-sky catalogue of 39 800 hot subluminous star candidates selected in Gaia DR2 by means of colour, absolute magnitude, and reduced proper motion cuts. We expect the majority of the candidates to be hot subdwarf stars of spectral type B and O, followed by blue horizontal branch stars of late B-type (HBB), hot post-AGB stars, and central stars of planetary nebulae. The contamination by cooler stars should be about 10%. The catalogue is magnitude limited to Gaia G < 19 mag and covers the whole sky. Except within the Galactic plane and LMC/SMC regions, we expect the catalogue to be almost complete up to about 1.5 kpc. The main purpose of this catalogue is to serve as input target list for the large-scale photometric and spectroscopic surveys which are ongoing or scheduled to start in the coming years. In the long run, securing a statistically significant sample of spectroscopically confirmed hot subluminous stars is key to advance towards a more detailed understanding of the latest stages of stellar evolution for single and binary stars.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Catalogs; Stars: horizontal-branch; Subdwarfs